ANALISIS TINGKAT KERAWANAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI KOTA BANDUNG PROVINSI JAWA BARAT DENGAN SISTEM INFORMASI GEOGRAFIS - Fanny Liesanty, - (2021)
This study aims to describe the level of vulnerability of dengue hemorrhagic fever (DHF), describe the pattern of dengue fever and to analyze the most affected factor for dengue fever in Bandung City. This research is a descriptive study with a quantitive approach assisted by Geographic Information System. Research variables include: (1) population density, (2) settlement density, (3) settlement pattern, (4) the buffer of river (5) the buffer of landfill (6) the buffer of tomb area. Data collection methods used imagery interpretation, documentation and observation. Data analysis techniques for determine the level od DHF susceptibility are scoring and GIS techniques (buffer and overlay), to determine the distribution pattern using analysis nearest neighbor and to determine the most affected factor of DHF using multiple linier regression analysis technique. The results : there are three classes of DHF susceptibility levels, they were 'very vulnerable area' (2863 Ha) , 'vulnerablee area'(5074 Ha) and 'not vulnerable area' (183 Ha). The distribution pattern of DHF in Bandung City has a cluster pattern with 9987 of the ratio. And the most affected variable onn the distribution of DHF in Bandung is settlement pattern with an effective contribution value of 61.12%.The number of DHF cases in Bandung City is still relatively high, prevention continues to be carried out between the government and society in synergy to tackle this outbreak.